If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 5x + x = 90 Combine like terms: x + 5x = 6x 6x + x = 90 Combine like terms: 6x + x = 7x 7x = 90 Solving 7x = 90 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '7'. x = 12.85714286 Simplifying x = 12.85714286
| -7(z-1)=-6(z+4) | | 145(13+46-22)=y | | 2x+5-6x=-11 | | 7/8-5/2y=-3/4 | | 21-3y=-12x | | 8x-9x+2(-3x-4)= | | -9r+5r+9= | | (4x+7)+(5x-7)=90 | | 3(-4p+26)=-144 | | m+16.8=40 | | (x-4)(x-6x+5)= | | -1/4x-1/3=-3/5 | | 2/5x21 | | -2(t-4)+4t=7t-8 | | 3(-4p+26)=144 | | vf=vo+at | | (5x-2)(3x+7)= | | 4x-8y=-36 | | 11x^6(9x^7-5x^6+3)= | | 9+10=y | | 4b-2b=-2 | | 2x/5=4=12 | | 75=n+12 | | -3(r+1)=-12 | | 9=9-8 | | -n-1=-6 | | x+(x+2)+(x+3)+(x+4)=212 | | (5x^3+5x^2-4x-6)+(7x^3-2x^2-5x+1)= | | 5(g-7)=45 | | (x+4)x(x+4)=100 | | 3x+2=31 | | (3x-5)(5x-6)= |